2020
DOI: 10.1002/jbmr.4133
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate Use Is Protective of Radiographic Knee Osteoarthritis Progression Among those With Low Disease Severity and Being Non-Overweight: Data From the Osteoarthritis Initiative

Abstract: Antiresorptive medications have been explored for treating knee osteoarthritis (OA); however, little data exist on the effects of today's more potent nitrogen‐containing oral bisphosphonates on radiographic disease‐progression in patients with varying disease‐severity, especially those who are not overweight. The primary objective of this cohort study was to determine if the use of bisphosphonates is protective against 2‐year radiographic‐progression of knee OA in Osteoarthritis Initiative (OAI) participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 43 publications
(88 reference statements)
0
20
1
Order By: Relevance
“…However, BPs may be suitable for OA patients with high bone turnover (Vaysbrot et al, 2018). A recent report by Hayes et al (2020) suggested an early preventive effect of BPs for a subpopulation of OA patients (Hayes et al, 2020). Hayes et al (2020) identified 346 BP responsive end-users from 1,977 eligible women, and in this cluster of patients, administration of BPs showed a protective effect against radiographic knee OA progression.…”
Section: Inhibiting Osteoclasts In Subchondral Bonementioning
confidence: 99%
See 3 more Smart Citations
“…However, BPs may be suitable for OA patients with high bone turnover (Vaysbrot et al, 2018). A recent report by Hayes et al (2020) suggested an early preventive effect of BPs for a subpopulation of OA patients (Hayes et al, 2020). Hayes et al (2020) identified 346 BP responsive end-users from 1,977 eligible women, and in this cluster of patients, administration of BPs showed a protective effect against radiographic knee OA progression.…”
Section: Inhibiting Osteoclasts In Subchondral Bonementioning
confidence: 99%
“…A recent report by Hayes et al (2020) suggested an early preventive effect of BPs for a subpopulation of OA patients (Hayes et al, 2020). Hayes et al (2020) identified 346 BP responsive end-users from 1,977 eligible women, and in this cluster of patients, administration of BPs showed a protective effect against radiographic knee OA progression. The administration of BPs was particularly effective as early prevention for non-overweight patients, but less effective for those with more advanced disease or with higher weight-bearing stress (Hayes et al, 2020).…”
Section: Inhibiting Osteoclasts In Subchondral Bonementioning
confidence: 99%
See 2 more Smart Citations
“…We read with interest Zhou and colleagues' response (1) to our article on bisphosphonates' protective effect on knee osteoarthritis progression with data from the Osteoarthritis Initiative. (2) The authors raise important points on methodology and highlight the enthusiasm for examining subchondral bone properties among studies of knee osteoarthritis (OA).…”
Section: To the Editormentioning
confidence: 99%